Increasing human resource management productivity in construction projects based on PMBOK - Hossein Ghorbani; Mohsen Alviri; Samaneh Jadali (مهندسی و مدیریت ساخت)
The importance of human resources is an inescapable issue that its lack of proper management leads to many costs, on the other hand, its proper management will increase productivity in construction projects. Research shows that 22 to 24 percent of construction projects face to lack of productivity. Due to the importance of profitability of projects, productivity is one of the most important issues in the construction industry that should be considered. In this regard, in the present study, human resources as one of the key factors of productivity, will be addressed. In order to increase the productivity of human resource management, the main factors in this field are identified according to the PMBOK standard. The executive teams of Mehr housing project are considered as the statistical population of the study. The importance of each factor is determined by sending a questionnaire to these experts and the final prioritization is done by SPSS statistical analysis software. One of the main results of this prioritization in order to increase productivity is to reduce cost-time and increase quality and potential customers' satisfaction.